2015
DOI: 10.1177/0022034515598507
|View full text |Cite
|
Sign up to set email alerts
|

PLAP-1/Asporin Positively Regulates FGF-2 Activity

Abstract: PLAP-1 is an extracellular matrix protein that is predominantly expressed in the periodontal ligament within periodontal tissue. It was previously revealed that PLAP-1 negatively regulates bone morphogenetic protein 2 and transforming growth factor β activity through direct interactions. However, the interaction between PLAP-1 and other growth factors has not been defined. Here, we revealed that PLAP-1 positively regulates the activity of fibroblast growth factor 2 (FGF-2), a critical growth factor in tissue h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Asporin negatively regulates TGFβ and this leads to an increase in cell proliferation and a decrease in apoptosis. More recently it has been shown that ASPN regulates TLR2- and TLR4-induced inflammatory responses (Yamaba et al , 2015) and also positively regulates FGF2 activity (Awata et al , 2015). FGF2 is increased in prostate cancer compared to normal prostate tissue, and increased FGF2 is localised to the tumour stroma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asporin negatively regulates TGFβ and this leads to an increase in cell proliferation and a decrease in apoptosis. More recently it has been shown that ASPN regulates TLR2- and TLR4-induced inflammatory responses (Yamaba et al , 2015) and also positively regulates FGF2 activity (Awata et al , 2015). FGF2 is increased in prostate cancer compared to normal prostate tissue, and increased FGF2 is localised to the tumour stroma.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates BMP2, TGFβ and FGF2 activity through direct and indirect interactions (Kizawa et al , 2005; Yamada et al , 2007; Tomoeda et al , 2008; Awata et al , 2015) and also binds type II collagen (Kou et al , 2010). ASPN has been shown to play a role in invasion in breast cancer cells (Simkova et al , 2016) and control the invasion of tumour cells and CAFs in scirrhous type gastric cancer (Satoyoshi et al , 2014), both in vitro and in vivo via the CD44-Rac1 pathway (Satoyoshi et al , 2014).…”
mentioning
confidence: 99%
“…In gastric cancer, asporin contributes to metastasis through EGFR and ERK-CD44/MMP-2 pathways [9]. Awata et al demonstrated that asporin could directly bind to FGF-2 and form an FGF-2–FGFR1 complex [18]. Phosphorylated EGFR recruited multiple Src homology 2 domains and activated their downstreaming signaling pathways [19].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that PLAP-1, an extracellular matrix protein that is mainly expressed in the periodontal ligament, regulates BMP-2 and FGF-2 activity through direct interaction, and TGF-b through indirect interaction (Awata et al 2015). The functions of the bioactive molecule FGF-2, for instance, are regulated by PLAP-1 through the formation of the FGF-2-FGFR1 complex via direct binding (Awata et al 2015). The functions of the bioactive molecule FGF-2, for instance, are regulated by PLAP-1 through the formation of the FGF-2-FGFR1 complex via direct binding (Awata et al 2015).…”
Section: The Role Of Bioactive Molecules In Physiological and Patholomentioning
confidence: 99%